2017
DOI: 10.1186/s12967-017-1205-9
|View full text |Cite
|
Sign up to set email alerts
|

Bovis Bacillus Calmette–Guerin (BCG) infection induces exosomal miRNA release by human macrophages

Abstract: BackgroundTuberculosis (TB) remains a significant global health concern and its diagnosis is challenging due to the limitations in the specificity and sensitivity of the current diagnostic tests. Exosomes are bioactive 30–100 nm vesicles produced by most cell types and are found in almost all human body fluids. Exosomal microRNAs (miRNAs) can transfer biological information between cells and tissues and may act as potential biomarkers in many diseases. In this pilot study, we assessed the miRNA profile of exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 68 publications
(81 reference statements)
3
62
0
4
Order By: Relevance
“…These would include CD9, CD63, and CD81 if the exosome was endosomal in origin [ 8 ]. Exosomes can, therefore, significantly affect target cell function resulting in the development of a pathological state [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These would include CD9, CD63, and CD81 if the exosome was endosomal in origin [ 8 ]. Exosomes can, therefore, significantly affect target cell function resulting in the development of a pathological state [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 Likewise, upon infection of macrophages with Mycobacterium bovis Bacillus Calmette-Guerin (BCG), the miRNA content of macrophage-derived exosomes is altered. 40 In silico analysis suggested that the differentially expressed exosomal miRNAs may subvert host metabolic pathway to enable BCG survival within infected macrophages. 40 Evidence has also suggested that extracellular vesicles, which include exosomes, seem to play a role in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…40 In silico analysis suggested that the differentially expressed exosomal miRNAs may subvert host metabolic pathway to enable BCG survival within infected macrophages. 40 Evidence has also suggested that extracellular vesicles, which include exosomes, seem to play a role in IBD. The extracellular vesicles purified from the intestinal lumen of IBD patients convey a higher amount of IL-6, IL-8, IL-10 and TNF-α compared to those from healthy subjects, and the levels of these pro-inflammatory mediators were positively correlated with CD severity score.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that miRNA-625-3p in the blood facilitated the detection of malignancy in benign lung tumors 34 , and miRNA-625-3p is reportedly upregulated in the urine of pulmonary TB patients and is an excellent diagnostic urinary biomarker 35 . miR-4732-3p is associated with breast cancer and stomach cancer and is specifically expressed in exosomes released from macrophages after infection with BCG 20,36 . We hypothesized that differential expression of these miRNAs in patients with NTM-PD and healthy controls would result in differences of target mRNA expression; thus, additional experimental validation is further required.…”
Section: Discussionmentioning
confidence: 99%